UPAYA MENINGKATKAN PRESTASI BELAJAR IPS MELALUI PEMBELAJARAN KOOPERATIF TEKNIK MAKE A MATCH SISWA KELAS V MI MIRAQITTA’LIMAT BAKAN - Yuliani, Meri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
Efforts to Improve Social Studies Learning Achievement Through Cooperative Learning Make A Match Techniques for Class V MI Miraqitta’limat Bakan Students. The background of this research is the low social studies learning achievement of the fifth grade students of MI Miraqitta’limat Bakan in the first semester of the 2020/2021 academic year, which is caused by the monotonous way of teaching social studies subject teachers, less attractive and less active for all students in the learning process so that students become less motivated to learn and have difficulty understanding social studies subject matter. The problems in this research are: How are the Efforts to Improve Social Studies Learning Achievement through Cooperative Learning of Make A Match Techniques for MI Miraqitta’limat Bakan Class Students for the 2020/2021 Academic Year. This study aims to improve the social studies learning achievement of the fifth grade students of MI Miraqitta’limat Bakan for the 2020/2021 academic year through Cooperative Learning of the Make A Match Technique. This study involved 19 fifth grade students as subjects. The indicator of achievement in this research is if the learning achievement in the cognitive aspects of students increases from cycle I to cycle II. The results of the observation of teaching and learning activities have increased from each cycle. In the process of learning the technique of looking for a partner, students are grouped heterogeneously, students are divided into two groups, namely the question card holder group and the answer card holder group. Students group according to the pairs of cards they get. Group members discuss solving problems assigned by the teacher then students are randomly selected to explain the results of their group discussions in front of the class. Student learning achievement in the cognitive aspect has increased from the previous cycle, namely in the first cycle, 68.2% increased to 89.4% in the second cycle and in the psychomotor aspect observed through student learning activities also experienced an increase from the previous cycle, from 80 categorized as very active. to 94 in the very active category. Thus Cooperative Learning of the Make A Match Technique can Improve Social Studies Learning Achievement in Class V MI Miraqitta’limat Bakan Students for the 2020/2021 Academic Year.